Educational and Fun? Parent Versus Preschooler Perceptions and Co-Use of Digital and Print Media. (July 2019) - Strouse, Gabrielle A.; Newland, Lisa A.; Mourlam, Daniel J.
This study was designed to assess parental beliefs, motivations, and facilitative co-use of print and digital media with preschoolers and identify differences between parents' and children's perceptions of these media. We surveyed 43 parents and interviewed their 3- to 5-year-old children. Parents reported their child enjoyed print more than digital books and predicted their child would choose a print over a digital book. Parents indicated they believed print was more educational and entertaining than digital media and were motivated to use print for children's learning, relaxation, entertainment, and parent-child bonding. Parents also reported they use fewer facilitative behaviors when co-using digital than print media. Children more often chose to read the digital over the print book and more often selected digital devices across most motives. This study highlights a contrast between how parents and children view media and suggests that parents might better facilitate children's digital media use by creating more interactive digital media co-use opportunities.